2011
DOI: 10.4137/cmc.s6130
|View full text |Cite
|
Sign up to set email alerts
|

Complete Recovery of Ischemic Cardiomyopathy from Thrombotic Thrombocytopenic purpura

Abstract: A 50 year old male HIV patient on antiretroviral therapy was admitted for chest pain. Upon admission, the patient was found to have elevated cardiac enzymes, acute thrombocytopenia, hemolytic anemia, acute pancreatitis and acute renal failure. The patient was diagnosed with thrombotic thrombocytopenic purpura/haemolytic uremic syndrome and emergency plasma exchange therapy was initiated along with aspirin, beta-blockers, steroids, and antiretroviral therapy. Patient responded well and demonstrated complete res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…On multivariate analysis, however, only troponin I remained significantly associated with death. Myocardial ischemia, cardiac events immediately prior to death, autopsy confirmation of platelet‐rich thrombi (as seen in 3 of our patients), and impaired left ventricular systolic function were also noted in previous publications …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On multivariate analysis, however, only troponin I remained significantly associated with death. Myocardial ischemia, cardiac events immediately prior to death, autopsy confirmation of platelet‐rich thrombi (as seen in 3 of our patients), and impaired left ventricular systolic function were also noted in previous publications …”
Section: Discussionsupporting
confidence: 87%
“…Cardiac ischemia in patients with TTP has been well‐documented for almost 50 years, and recent studies have seen an association between cardiac markers and worse outcomes . In addition to symptoms and electrocardiographic signs of acute myocardial infarction (AMI), serum biomarkers are used to confirm myocardial necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although coronary artery thrombosis in TTP has been reported in several autopsy studies, cardiac complications of TTP, including ischemic cardiomyopathy, have rarely been reported (1)(2)(3). We herein report a case of ischemic cardiomyopathy with a rapid progression from TTP.…”
Section: Introductionmentioning
confidence: 85%
“…Plasma exchange therapy is the standard treatment for TTP. The mortality associated with TTP has decreased from 90% to less than 20% due to the initiation of plasma exchange therapy (3,12,13). Gaddam et al reported complete recovery of ischemic cardiomyopathy from TTP using plasma exchange therapy (3).…”
Section: Discussionmentioning
confidence: 99%
“…She is receiving methylprednisolone 6 mg day −1 and azathioprine 150 mg day −1 . The final diagnosis was TTP with a possible overlap with haemolytic-uraemic syndrome (HUS), as more frequently described in women and blacks (Gaddam et al, 2011). An association of SLE with TTP has been described since several years, while the relationship with low ADAMTS-13 activity is more recently reported (Yamada et al, 2011).…”
mentioning
confidence: 99%